2021
DOI: 10.1155/2021/2140151
|View full text |Cite
|
Sign up to set email alerts
|

Detection of High- and Low-Risk HPV DNA in Archived Breast Carcinoma Tissues from Ethiopian Women

Abstract: Background. Human papilloma virus (HPV) is involved in the development of cancer of the cervix, mouth and throat, anus, penis, vulva, or vagina, but it has not been much considered as a cause of breast cancer. Recently, a number of investigations have linked breast cancer to viral infections. High-risk HPV types, predominantly HPV types 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, and 59, are established as carcinogens in humans. In this study we aimed to detect 19 high-risk and 9 low-risk HPVs from archived br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…Non-malignant breast tumors had a higher HPV percentage (29.6%) than breast cancer (20.6%), which may suggest that there is no association between HPV infection and breast cancer. Another earlier study found that HPV was present in 2.7% of Ethiopian breast cancer cases [34] which is a far lower number than the current study. The percentage of HPV positivity was higher in…”
Section: Discussioncontrasting
confidence: 87%
“…Non-malignant breast tumors had a higher HPV percentage (29.6%) than breast cancer (20.6%), which may suggest that there is no association between HPV infection and breast cancer. Another earlier study found that HPV was present in 2.7% of Ethiopian breast cancer cases [34] which is a far lower number than the current study. The percentage of HPV positivity was higher in…”
Section: Discussioncontrasting
confidence: 87%
“…HPV genotypes 16 and 18 are the most common virus types found in cancers worldwide ( 32 ). However, other types of HPV including 6, 11, 33, 35, 39, 45, 51 and 59 have also been detected in breast cancer patients ( 33 ). Two meta-analyses showed a higher prevalence of high-risk HPVs, including 16, 18 and 33, compared to other HPV strains.…”
Section: Discussionmentioning
confidence: 99%
“…Viral etiology of breast carcinoma has been addressed in numerous studies, but still remains controversial ( 9 ). Several viruses, including bovine leukemia virus, Kaposi's sarcoma-associated herpesvirus, Epstein-Barr virus (EBV), mouse mammary tumor virus (MMTV), simian vacuolating virus 40 ( 10 ), human mammary tumor virus ( 11 ), cytomegalovirus (CMV) ( 12 ), herpes simplex virus-1 (HSV), human herpes virus type-8 ( 13 ) have been regarded as potential breast oncogenic factors a number of years ago. In 1944, the discovery that MMTV caused BC in mice led researchers to investigate a possible viral contribution to BC ( 14 ).…”
Section: Introductionmentioning
confidence: 99%